Women's knowledge and attitudes regarding cervical cancer screening - Florencia Vicente Chiconela; José Braz Chidassicua (Universidade Federal de Goias, 2017)
This study aimed to evaluate women's knowledge and attitudes regarding the importance of cervical cancer screening. This is a descriptive, exploratory, with a qualitative approach study, carried out with 14 women assisted at a health service in Mozambique. Data collection occurred with a semi-structured interview from February to March 2015. The results were analyzed using the content analysis technique. Although most women have heard of cervical cancer (CC) on television and in hospital lectures, they have little knowledge about prevention, are unaware of the importance of the screening and have the exam due to gynecological complaints. Women's knowledge is incipient and below the expectations about the importance of the screening.